Positive electrode active material, method for producing the same, and use thereof
Patent Information
- Application Number
- CN202610337087.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-03-19
AI Technical Summary
尽管快离子导体包覆可兼顾界面保护与离子传输,但其制备过程通常需额外引入锂源(如LiNO3、LiOH),增加了工艺复杂性与成本
(1)变废为宝,资源化利用:创造性地将传统工艺中必须去除的有害残碱(Li2CO3/LiOH)转化为合成高性能Li3mLa2/3-mTiO3包覆层所必需的锂源,实现了锂资源的原位循环利用,彻底消除了残碱危害,同时省略了额外锂盐添加和复杂水洗步骤,大幅降低生产成本,简化工艺流程。
Smart Images

Figure CN122202252B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a positive electrode active material, its preparation method, and its application. Background Technology
[0002] Ultra-high nickel single-crystal LiNixCoyMn1-x-yO2 (x≥0.9) cathode material is considered one of the key materials for building next-generation high-energy-density lithium-ion batteries due to its advantages such as high specific capacity, no grain boundary structure, excellent mechanical stability and low specific surface area. However, this material still faces a series of severe challenges in the process of industrialization: (1) High residual alkali content on the surface: During the preparation and storage process, a large amount of Li2CO3 and LiOH residues are easily formed on the surface of the material. These alkaline substances will exacerbate electrolyte decomposition, causing problems such as gas production and battery swelling, and significantly increase interfacial impedance, thereby seriously affecting the cycle life and safety performance of the battery; (2) Poor interfacial stability: Highly active surfaces are prone to side reactions with electrolyte, forming an unstable and excessively thick cathode electrolyte interface (CEI) film, which continuously consumes active lithium and electrolyte, resulting in rapid capacity decay; (3) Bulk structure degradation: Under high-voltage deep delithiation, the material undergoes an irreversible phase transition from H2 phase to H3 phase, accompanied by lattice distortion and the initiation and propagation of microcracks, eventually leading to structural failure; (4) Slow ion diffusion kinetics: Micron-sized single crystal particles significantly prolong the solid-phase diffusion path of lithium ions, resulting in its rate performance usually being inferior to that of nano-polycrystalline materials.
[0003] To address these issues, commonly used strategies include surface coating and bulk doping. Surface coating (such as Al2O3, Li2ZrO3, etc.) can physically block the contact between the electrolyte and the active material, but most coating materials have low ionic conductivity, often sacrificing the material's rate performance. Although coating fast ion conductors can balance interface protection and ion transport, its preparation process usually requires the introduction of an additional lithium source (such as LiNO3, LiOH), increasing process complexity and cost. Bulk doping (such as Mg, Al, Ti, Zr, etc.) enhances structural stability by strengthening lattice bond energy, but it is difficult to improve interface problems. In addition, existing modification processes mostly adopt a stepwise approach, i.e., first performing water washing to remove alkali or doping sintering, then performing coating and secondary heat treatment, which is cumbersome and inefficient. The water washing process is particularly unfriendly to single-crystal materials, which may cause surface corrosion, transition metal dissolution, and lithium loss, while the physical coating layer has weak adhesion to the substrate and is prone to peeling off during long-term cycling, affecting the durability of the coating effect.
[0004] Therefore, developing a method that can synergistically address the issues of residual alkali, interface, bulk phase, and kinetics in ultra-high nickel single crystal materials, utilize residual alkali resources, and achieve interface coating and bulk phase doping modification in one step is of great significance for promoting the application of this type of material in high-performance lithium-ion batteries. Summary of the Invention
[0005] This invention provides a positive electrode active material, its preparation method, and its application.
[0006] The first aspect of the present invention provides a positive electrode active material, comprising matrix particles and a coating layer covering the surface of the matrix particles. The chemical composition of the matrix particles is LiNixCoyMn1-x-yO2, x≥0.9, and the chemical composition of the coating layer is Li3mLa2 / 3-mTiO3, 0<m<0.5. Furthermore, Ti element is doped from the surface of the positive electrode active material to the interior within a range of 500nm, and the concentration of Ti element gradually decreases.
[0007] As described above, the thickness of the coating layer in the positive electrode active material is 2-50 nm; specifically, it can be within the range of 2 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, 42 nm, 45 nm, 48 nm, 50 nm, or any combination thereof. It is understood that the thickness value of the coating layer at any location on the surface of the matrix particles is not unique, but it should all be within the above range.
[0008] As described above, in the XRD spectrum of the positive electrode active material, the (006) / (102) diffraction peak and the (108) / (110) diffraction peak are split, indicating that it has a layered structure.
[0009] The positive electrode active material as described above has a particle size of 0.5-5 μm; specifically, it can be 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5.0 μm, or within any two of these ranges.
[0010] A second aspect of the present invention provides a method for preparing any of the above-described positive electrode active materials, comprising the following steps: S1. Provide matrix particles, the surface of which contains Li2CO3 and LiOH, and the chemical composition of which is LiNixCoyMn1-x-yO2, x≥0.9; S2. A coating layer precursor is formed on the surface of the matrix particles to obtain a positive electrode active material precursor, wherein the coating layer precursor includes a La source and a Ti source; S3. The positive electrode active material precursor is calcined in an oxygen-containing gas atmosphere to obtain the positive electrode active material.
[0011] This invention uses ultra-high nickel single-crystal LiNixCoyMn1-x-yO2 (where x≥0.9) as the matrix particles to provide high specific capacity for the positive electrode active material. Subsequently, a dense, highly conductive crystalline lithium lanthanum titanium oxide (Li3mLa2 / 3-mTiO3) coating layer is formed on the surface of the matrix particles through a high-temperature in-situ reaction. This coating layer effectively isolates the electrolyte from direct contact with the highly active matrix, suppresses interfacial side reactions, and provides a channel for rapid lithium-ion transport. During the high-temperature heat treatment, some Ti4+ diffuses from the precursor into the matrix, entering the crystal lattice to form dopant, with its concentration decreasing gradually from the surface to the interior. This gradient doping layer enhances the structural stability of the surface lattice, suppresses the H2-H3 phase transition and microcrack formation, and achieves atomic-level strong bonding with both the core matrix and the outer coating layer, ensuring the mechanical and electrochemical stability of the entire structure. The structure of the prepared positive electrode active material is as follows: Figure 1 As shown, a one-step method is used to simultaneously achieve surface coating and bulk gradient doping, solving the problems of residual alkali, interface, bulk phase and kinetics in ultra-high nickel single crystal materials.
[0012] In the preparation method described above, the mass of Li2CO3 on the surface of the matrix particles is 0.05-0.5% of the total mass of the matrix particles, specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, or within any two of these ranges. The mass of LiOH on the surface of the matrix particles is 0.02-0.3% of the total mass of the matrix particles, specifically within the range of 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, or any combination thereof. Excessive residual alkali content on the surface of the matrix particles will affect the electrochemical performance of the material.
[0013] As described above, the content of Li₂CO₃ and LiOH on the surface of the matrix particles can be detected by a two-step titration method. Specifically, the steps are as follows: 1. Sampling: Accurately weigh a certain mass of the positive electrode material. 2. LiOH content determination (first-step titration): Quickly disperse the sample in deionized water that has been purged with Ar gas to remove CO₂, and immediately titrate with standard hydrochloric acid solution, using phenolphthalein as an indicator. Record the volume of hydrochloric acid consumed in the first step, V₁ (V₁ mainly corresponds to the LiOH content). 3. Li₂CO₃ content determination (second-step titration): Add an excess of a known volume of the same standard hydrochloric acid solution to the same solution, stir thoroughly or sonicate to ensure all Li₂CO₃ reacts completely: Li₂CO₃ + 2HCl → 2LiCl + CO₂ + H₂O. Then back-titrate the remaining hydrochloric acid in the solution with standard sodium hydroxide solution, using bromophenol blue or methyl orange as an indicator, and record the volume of sodium hydroxide consumed in the second-step back-titration, V₂. By calculating the total amount of hydrochloric acid added and the amount of hydrochloric acid remaining (corresponding to V2), the amount of hydrochloric acid used to neutralize Li2CO3 can be calculated, thus obtaining the content of Li2CO3.
[0014] In the preparation method described above, the La source includes at least one of lanthanum nitrate, lanthanum acetate, and lanthanum oxide; the Ti source includes at least one of tetrabutyl titanate, titanium oxysulfate, and titanium dioxide.
[0015] In the preparation method described above, in S2, the coating layer precursor is obtained by sol-gel method, liquid phase deposition method or spray coating method.
[0016] In the preparation method described above, in step S3, the calcination conditions are as follows: the temperature is increased to 600-900 °C at a heating rate of 2 °C / min-6 °C / min, and held at 600-900 °C for 4-24 hours. Within this temperature range and in an oxygen atmosphere, Ti⁴⁺ diffuses from the LLTO coating layer into the NCM matrix, and the diffusion rate is positively correlated with the lithium vacancy concentration on the matrix surface, which is in turn affected by the decomposition rate of residual alkali on the surface. By controlling the heating rate and holding time, the diffusion depth and concentration gradient distribution of Ti can be precisely controlled.
[0017] A third aspect of the present invention provides a battery comprising any of the above-described positive electrode active materials.
[0018] The battery described above is a lithium-ion battery.
[0019] Compared with the prior art, the present invention has the following significant advantages: (1) Turning waste into treasure and making resources: The harmful residual alkali (Li2CO3 / LiOH) that must be removed in the traditional process is creatively transformed into the lithium source necessary for the synthesis of high-performance Li3mLa2 / 3-mTiO3 coating layer, realizing the in-situ recycling of lithium resources, completely eliminating the harm of residual alkali, and at the same time omitting the additional lithium salt addition and complex water washing steps, greatly reducing production costs and simplifying the process.
[0020] (2) Integrated Synergy, Dual Modification: Through one-step high-temperature heat treatment, the in-situ synthesis of Li3mLa2 / 3-mTiO3 coating layer and the gradient bulk doping of Ti element were completed simultaneously, realizing the dual synergistic strengthening of material interface and bulk phase, overcoming the problems of complex traditional step-by-step modification process, weak interface bonding and single function.
[0021] (3) Structural innovation and comprehensive performance improvement: A unique "core-gradient-shell" composite structure has been formed. The core is an ultra-high nickel single crystal LiNixCoyMn1-x-yO2 matrix, the outer shell is a dense and highly ionicly conductive Li3mLa2 / 3-mTiO3 coating layer, and the middle is a transition interface of Ti-doped ultra-high nickel single crystal LiNixCoyMn1-x-yO2. This structure simultaneously solves multiple problems such as interfacial side reactions, bulk phase transition, and slow ion diffusion, enabling the material to have high capacity, long cycle life, excellent rate performance, and high-temperature safety.
[0022] (4) Strong bonding and excellent stability: The Li3mLa2 / 3-mTiO3 coating layer generated by high-temperature in-situ reaction has a strong chemical bond with the substrate, and the Ti gradient doping layer has achieved atomic-level fusion with the substrate. The interfacial bonding force is far superior to the coating layer formed by physical mixing or low-temperature annealing, ensuring the long-term stability of the modification effect. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the structure of the positive electrode active material provided by the present invention; Figure 2 The XRD pattern of the positive electrode active material provided in Example 1 of this invention; Figure 3 FESEM image of the positive electrode active material provided in Example 1 of this invention; Figure 4 This is a TEM image of the positive electrode active material provided in Example 1 of the present invention; Figure 5 The Ti 2p XPS spectra of the positive electrode active material provided in Example 1 of the present invention at different sputtering depths are shown. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, embodiments of this invention, and should not be construed as limiting the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention. In the description of this invention, it should be understood that the terminology used is for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0025] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0026] Example 1: Preparation of positive electrode active material S1. Provides ultra-high nickel single crystal matrix particles: The single-crystal LiNi0.95Co0.02Mn0.03O2 cathode material prepared by co-precipitation-high-temperature sintering was placed in a vacuum drying oven and dried at 120℃ for 12 hours to remove adsorbed water. The surface of the matrix particles contained 0.18 wt% Li2CO3 and 0.11 wt% LiOH residues. The contents of Li2CO3 and LiOH were determined by a two-step titration method.
[0027] Construction of the S2.Li0.33La0.56TiO3 precursor layer: According to the stoichiometric ratio of Li0.33La0.56TiO3, 0.330 g of lanthanum nitrate (La(NO3)3·6H2O) and 0.463 g of tetrabutyl titanate (C16H36O4Ti) were dissolved in 50 ml of anhydrous ethanol, and 0.6 g of citric acid was added as a complexing agent. The mixture was stirred to form a homogeneous sol. 5.0 g of the dried single-crystal LiNi0.95Co0.02Mn0.03O2 matrix powder from step S1 was weighed and slowly added to the sol. The mixture was continuously stirred and heated to 80°C to allow the solvent to gradually evaporate. After the reaction was completed, the resulting powder was dried at 120°C for 6 hours to obtain single-crystal LiNi0.95Co0.02Mn0.03O2 matrix particles coated with the Li0.33La0.56TiO3 precursor.
[0028] S3. One-step high-temperature heat treatment: The powder was placed in a tube furnace and heated to 800 °C at a heating rate of 5 °C / min under an oxygen atmosphere, and held at this temperature for 10 hours. During this process, Li₂CO₃ / LiOH on the surface of the single-crystal LiNi₀.95Co₀.02Mn₀.03O₂ matrix particles underwent an in-situ solid-state reaction with the decomposition products of La and Ti precursors (La₂O₃, TiO₂), forming a crystalline perovskite-type Li₀.33La₀.56TiO₃ coating layer. Simultaneously, driven by the high temperature, some Ti⁴⁺ diffused from the coating layer precursor into the interior of the single-crystal LiNi₀.95Co₀.02Mn₀.03O₂ matrix particles, entering the lattice and in-situ replacing Ni²⁺ / Ni³⁺ sites, forming a Ti gradient doped layer with a gradually decreasing concentration from the surface to the interior. After the reaction was completed, the material was naturally cooled to room temperature to obtain the positive electrode active material.
[0029] The positive electrode active material prepared in Example 1 was subjected to XRD detection, and the detection results are as follows: Figure 2 As shown. According to Figure 2 It can be seen that all diffraction peaks are in good agreement with the standard spectrum of typical α-NaFeO2 layered structure (space group: R-3m). Among them, the (006) / (102) and (108) / (110) diffraction peak pairs are clearly split, indicating that the material has a highly ordered layered crystal structure and that the modification treatment did not destroy the structural integrity of the matrix material itself. No obvious characteristic diffraction peaks of Li0.33La0.56TiO3 were observed in the spectrum, which may be due to the low content of the coating layer, which is below the XRD detection limit.
[0030] The positive electrode active material prepared in Example 1 was observed using field emission scanning electron microscopy (FESEM), and the results are as follows: Figure 3 As shown, the material exhibits a typical single-crystal morphology, with irregular but uniformly dispersed particle shapes. The particle size is mainly distributed in the range of 2-4 μm, demonstrating good monodispersity and no obvious sintering or agglomeration. The sample particles show a distinctly rough morphology, which may be related to the Li0.33La0.56TiO3 coating layer formed on their surface.
[0031] The positive electrode active material prepared in Example 1 was observed using transmission electron microscopy (TEM), and the results are as follows: Figure 4 As shown in the figure, a continuous and dense Li0.33La0.56TiO3 coating layer with an average thickness of approximately 5 nm can be clearly observed on the surface of the matrix particles. This coating layer is tightly bonded to the matrix interface, exhibiting good coverage and structural integrity.
[0032] The positive electrode active material prepared in Example 1 was observed using X-ray photoelectron spectroscopy, and the results are as follows: Figure 5As shown, characteristic peaks at 458.6 eV (Ti 2p3 / 2) and 464.3 eV (Ti 2p1 / 2) are clearly observed on the initial surface (0 nm). The binding energy positions indicate that titanium exists in the Ti4+ state, consistent with the chemical environment of titanium in the Li0.33La0.56TiO3 coating layer. As the etching depth increases from 0 nm to 100 nm, the Ti 2p signal intensity shows a continuous and obvious gradient decay trend. This result directly confirms that Ti element exhibits a concentration gradient distribution from the material surface to the bulk phase, consistent with the "gradient doping" structural characteristics designed in this invention.
[0033] Example 2: Preparation of positive electrode active material The preparation method of the positive electrode active material provided in this embodiment can be referred to in Embodiment 1, except that the heat treatment temperature in step 3 is 700 ℃.
[0034] Example 3: Preparation of positive electrode active material The preparation method of the positive electrode active material provided in this embodiment can be referred to in Example 1. The difference is that in step 1, the matrix particles are LiNi0.9Co0.05Mn0.05O2 (the surface of which contains 0.14 wt% Li2CO3 and 0.09 wt% LiOH residue, and the changes in the content of surface Li2CO3 and LiOH are mainly obtained by exposing the material to air for different times); in step 2, the amounts of La(NO3)3·6H2O, C16H36O4Ti and citric acid added are 0.266 g, 0.373 g and 0.45 g, respectively, and the remaining steps are the same as in Example 1.
[0035] Example 4: Preparation of positive electrode active material The preparation method of the positive electrode active material provided in this embodiment can refer to Embodiment 1. The difference is that in step 2, the spray coating method is used instead of the sol-gel method to construct the precursor layer. 0.241 g of lanthanum acetate (C6H9LaO6) and 0.218 g of titanium oxysulfate (TiOSO4) are dissolved in deionized water to form a uniform solution. The solution is then uniformly sprayed onto the surface of the single crystal substrate using a spray drying device.
[0036] Example 5: Preparation of positive electrode active material The preparation method of the positive electrode active material provided in this embodiment can refer to Example 1. The difference is that in step 2, the amount of La(NO3)3·6H2O, C16H36O4Ti and citric acid added is changed to 0.225 g, 0.340 g and 0.5 g, respectively, and the chemical composition of the coating layer is Li0.45La0.52TiO3.
[0037] Comparative Example 1: Preparation of Positive Electrode Active Material The positive electrode active material provided in this comparative example is the original single-crystal LiNi0.95Co0.02Mn0.03O2 matrix material, without any coating or doping treatment.
[0038] Comparative Example 2: Preparation of Positive Electrode Active Material The single-crystal LiNi0.95Co0.02Mn0.03O2 matrix of Example 1 was washed and dried with deionized water to remove residual alkali from the surface. Then, following steps 2 and 3 of Example 1, but with the addition of 0.031 g of lithium ethoxide as a lithium source to the sol, Li0.33La0.56TiO3 coating was performed.
[0039] Comparative Example 3: Preparation of Positive Electrode Active Material The single-crystal LiNi0.95Co0.02Mn0.03O2 matrix of Example 1 was ground and mixed with nano-titanium dioxide (TiO2) in a mortar for 2 hours. Then, the mixed powder was heated to 800°C at 5°C / min and kept at that temperature for 12 hours under an oxygen atmosphere. After natural cooling, grinding and sieving, Ti bulk doped positive electrode active material was obtained.
[0040] Comparative Example 4: Preparation of Positive Electrode Active Material Following the method described in steps 1-2 of Example 1, single-crystal LiNi0.95Co0.02Mn0.03O2 matrix particles coated with Li0.33La0.56TiO3 precursor were placed in a tube furnace and heated to 550 °C at a heating rate of 3 °C / min under an oxygen atmosphere, and held at this temperature for 6 hours. At this heat treatment temperature, only the coating layer is formed, and there is no Ti gradient doping, resulting in Li0.33La0.56TiO3-coated single-crystal LiNi0.95Co0.02Mn0.03O2 positive electrode active material.
[0041] 2032 Button Cell Assembly and Performance Testing Preparation of positive electrode: The positive electrode active material to be tested, acetylene black and polyvinylidene fluoride (PVDF) binder were mixed in a mortar at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was then thoroughly ground to form a slurry. The slurry was then uniformly coated onto an aluminum foil current collector and dried under vacuum at 120 °C for 12 hours. The slurry was then pressed into discs with a diameter of 12 mm by roller pressing and punching. The mass of the active material of each electrode was accurately weighed and recorded to ensure the accuracy and comparability of subsequent tests.
[0042] Assembly of coin cells: The entire process was carried out in a strictly controlled argon atmosphere glove box (H2O, O2 < 0.1 ppm) to eliminate environmental interference. A stainless steel gasket and a high-purity lithium metal sheet were placed sequentially in the negative electrode shell of the 2032 battery, followed by the addition of 20 μL of electrolyte (1 M LiPF6 dissolved in EC / DEC / EMC, volume ratio 1:1:1). A Celgard 2320 separator was then placed on top, and another 20 μL of electrolyte was added to ensure thorough wetting. The prepared positive electrode sheet was then placed in the shell, and the positive electrode shell was closed, followed by a strict seal using a hydraulic sealer. After encapsulation, the battery was removed and allowed to stand at room temperature for 12 hours to allow for complete electrolyte penetration and interface stabilization.
[0043] Electrochemical and safety performance testing: Electrochemical testing was conducted using the Xinwei testing system at a constant temperature of 25 ℃ within a voltage window of 2.8–4.5 V. After activation at a low rate of 0.1 C for 3 weeks, the system was switched to 1 C for long-term cycling testing, and the capacity retention rate was recorded. Rate performance was assessed by increasing the current in steps from 0.1 C to 5 C, with 5-week cycles at each rate. Thermal safety was evaluated using differential scanning calorimetry (DSC). The electrode charged to 4.5 V was removed from the glove box and sealed in a high-pressure crucible. The heat flow changes in its reaction with the electrolyte were monitored at a certain heating rate. Key indicators included the exothermic onset temperature and the total heat release, which were used to comprehensively evaluate the thermal stability and safety boundary of the material. The results are shown in Tables 1-2.
[0044] Table 1. Performance test results of the battery provided by the present invention
[0045] Table 2. Thermal stability test results of the battery provided by the present invention
[0046] A comparison of Examples 1-5 with Comparative Example 1 shows that the cathode active material provided by this invention can effectively improve the initial coulombic efficiency, cycle life, and rate performance of ultra-high nickel single crystal cathode materials, thereby comprehensively improving the energy density, lifespan, and high-power application performance of the battery. Furthermore, the cathode active material provided by this invention can significantly increase the exothermic peak onset temperature and reduce the total heat release, improving the thermal stability of the material and thus greatly enhancing the safety performance of the battery.
[0047] The comparison between Example 1 and Comparative Example 2 shows that the "in-situ reaction using residual alkali" strategy adopted in this invention is superior to the traditional coating method of "adding lithium source after water washing to remove alkali" in terms of improving electrochemical performance and safety performance. This proves that the strategy simplifies the process while ensuring better overall performance.
[0048] The comparison between Example 1 and Comparative Examples 3-4 shows that the "coating and doping synergy" strategy adopted in this invention is significantly better than single bulk doping or single surface coating methods in improving the overall performance of the battery, proving the necessity and excellent effect of the synergistic modification strategy in solving the problems of interfacial side reactions and bulk structure degradation at the same time.
[0049] By comparing Examples 1, 4-5 and Comparative Example 1, it can be seen that the material performance can be effectively improved in all different coating methods and Li3mLa2 / 3-mTiO3 (0 < m < 0.5) composition ranges described in this invention, proving the universality and flexibility of the process route of this invention.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that, It includes matrix particles and a coating layer covering the surface of the matrix particles, wherein the chemical composition of the matrix particles is LiNi. x Co y Mn 1-x-y O2, x≥0.9, the chemical composition of the coating layer is Li 3m La 2 / 3- m TiO3, 0 < m < 0.5, and Ti element is doped from the surface of the positive electrode active material to the interior within a range of 500 nm, and the concentration of Ti element gradually decreases.
2. The positive electrode active material according to claim 1, characterized in that, The thickness of the coating layer is 2-50 nm.
3. The positive electrode active material according to claim 1, characterized in that, In the XRD spectrum of the positive electrode active material, the (006) / (102) diffraction peak and the (108) / (110) diffraction peak are split.
4. The positive electrode active material according to claim 1, characterized in that, The particle size of the positive electrode active material is 0.5-5 μm.
5. The method for preparing the positive electrode active material according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Provide matrix particles, the surface of which contains Li2CO3 and LiOH, and the chemical composition of which is LiNi. x Co y M n1-x-y O2, x≥0.9; S2. A coating layer precursor is formed on the surface of the matrix particles to obtain a positive electrode active material precursor, wherein the coating layer precursor includes a La source and a Ti source; S3. The positive electrode active material precursor is calcined in an oxygen-containing gas atmosphere to obtain the positive electrode active material.
6. The preparation method according to claim 5, characterized in that, The mass of Li2CO3 on the surface of the matrix particles is 0.05-0.5% of the total mass of the matrix particles, and the mass of LiOH on the surface of the matrix particles is 0.02-0.3% of the total mass of the matrix particles.
7. The preparation method according to claim 5, characterized in that, The La source includes at least one of lanthanum nitrate, lanthanum acetate, and lanthanum oxide; the Ti source includes at least one of tetrabutyl titanate, titanium oxysulfate, and titanium dioxide.
8. The method according to claim 5, characterized in that, In S2, the coating layer precursor is obtained by sol-gel method, liquid phase deposition method or spray coating method.
9. The method according to claim 5, characterized in that, In S3, the calcination conditions are as follows: the temperature is increased to 600-900 ℃ at a heating rate of 2 ℃ / min-6 ℃ / min, and then held at 600-900 ℃ for 4-24 hours.
10. A battery, characterized in that, Includes the positive electrode active material as described in any one of claims 1-4.
Citation Information
Patent Citations
Coated modified high-nickel ternary positive electrode material, preparation method and lithium ion battery
CN120453330A
Lithium nickel manganese oxide positive electrode material and preparation method thereof, lithium ion battery and electric equipment
CN121416460A
